Marketing Mix Strategy to Improve Credit Performance at PT BPR Bank Tulungagung Perseroda - Suhermin Suhermin; Basuki Rachmat (Transpublika Publisher, 2026)
Rural banks (BPRs) in Indonesia face mounting pressure from intensifying competition, fintech disruption, and suboptimal credit performance that threatens their financial stability and role in supporting local economic growth. This study examines the effect of the marketing mix strategy, consisting of product, price, place, promotion, people, process, and physical evidence, on credit performance at PT BPR Bank Tulungagung Perseroda. Despite the growing importance of marketing strategy in rural bank (BPR) performance, empirical evidence on which marketing mix dimensions most directly drive credit outcomes remains limited. A quantitative approach with a causality-based research design was used to examine the relationships among the variables. Data were collected through structured questionnaires administered to 340 respondents, including bank customers and staff, and analyzed using IBM SPSS Statistics 25. Before the main analysis, all instruments were tested for validity and reliability; all items were valid, with r-values exceeding the r-table threshold of 0.106 at a significance level below 0.05, and reliable, with Cronbach’s Alpha coefficients above 0.70. The results show that the marketing mix strategy simultaneously has a positive and significant effect on credit performance. Partially, product, promotion, and process are the most dominant variables influencing credit performance, suggesting that credit product quality, promotional effectiveness, and service process efficiency are key drivers of credit growth and quality. This study contributes practical guidance for BPR management to prioritize product innovation, service quality improvement, and credit process efficiency as part of an integrated marketing strategy to sustain competitiveness and credit performance.